Influence Of 3-(3-Fluorophenyl)-6-(4-Methoxyphenyl)-7H-[1,2,4]-Triazolo-[3,4-B][1,3,4]Thiadiazine On The Cultural Properties Of Pathogenic Mycobacterium Bovis - Bihdan, O. А.; Parchenko, V. V.; Zazharskyi, V.; Fotina, T.; Davydenko, P.; Бігдан, Олексій Антонович; Парченко, Володимир Володимирович (My University, 2018)
Derivatives of 1,2,4-triasole are widely used in many fields of human activity. Regular creation of new and modern drugs. The outstanding scientists are actively working in this direction and this gives its results. Today, the treatment and prevention of many types of tuberculosisis a priority task in many countries around the world. The purpose of our work is to investigate the effect of 3- (3-fluorophenyl) -6- (4-methoxyphenyl) -7H- [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazine on the cultural properties of pathogenic Mycobacteriumbovis. Having analyzed the results of the conducted studies, the effect of 3- (3-fluorophenyl) -6- (4-methoxyphenyl) -7H- [1,2,4] triazolo [3,4-b] [1,3,4] thiadiazine on the cultural properties of pathogenic Mycobacteriumbovis.
Keywords: 3-(3-fluorophenyl)-6-(4-methoxyphenyl)-7H-[1,2,4]-triazolo-[3,4-b][1,3,4] thiadiazine; antituberculor activity; pathogenic strains